The Determinants of Foreign Direct Investment Inflows of Gansu Province China - YUXIA, Hu (Asian Journal of Empirical Research, 2013)
Foreign direct investment has contributed significantly to Chinese economic development. Yet the geographic distribution of FDI is quite uneven. Compared with the inward FDI in the eastern and mid regions of China, the Western region has attracted less FDI. FDI is fuelling much of the rapid economic leap of the developed regions of China and the significant inequity grows further. There are many determinant factors to influence the FDI inflows. The essay takes Gansu province as an example, the author concludes that the core constraining factors of Gansu province in FDI attraction are, but not limited to, the economy development and openness degree, natural environment and the impact of industrial cluster, thus, the government of Gansu province should formulate corresponding measures to attract FDI inflows so as to produce optimal results and stimulate the economy growth.